2023
DOI: 10.1107/s1600576723000547
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous small-angle X-ray scattering analyses on hierarchical structures of rubber–filler systems

Abstract: The hierarchical structures of poly(styrene-ran-butadiene) (SBR) rubber/carbon black (CB) systems vulcanized with sulfur and ZnO have been clarified using anomalous small-angle X-ray scattering (ASAXS) near the Zn absorption edge. In the case of SBR/CB systems vulcanized with peroxide, it has been found previously that the hierarchical structures formed by CB consist of aggregates of primary particles and agglomerates of those aggregates with mass-fractal dimensions. However, to date the hierarchical structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…For example, in the case of rubber-filler systems with sulfur and zinc oxide (ZnO), the K-absorption edge of Zn is used for ASAXS. Watanabe et al (2023) applied ASAXS to poly(styrene-ranbutadiene) (SBR)/carbon black (CB) systems vulcanized with sulfur and ZnO, and obtained the partial structure factors of CB and Zn separately. The results revealed that the CB aggregates comprise closely packed CB primary particles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of rubber-filler systems with sulfur and zinc oxide (ZnO), the K-absorption edge of Zn is used for ASAXS. Watanabe et al (2023) applied ASAXS to poly(styrene-ranbutadiene) (SBR)/carbon black (CB) systems vulcanized with sulfur and ZnO, and obtained the partial structure factors of CB and Zn separately. The results revealed that the CB aggregates comprise closely packed CB primary particles.…”
Section: Introductionmentioning
confidence: 99%